PENGARUH COVID-19 DAN PPKM TERHADAP USAHA MIKRO SEBAGAI SUMBER UTAMA PENDAPATAN KELUARGA - Handayani, Faroh; Triono, Firly Rio; Chairina, Nina (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2021)
The emergence of Covid-19 virus has impact on many sectors, which is economic sector. Economic sectors from small to large scale were also affected. Moreover, micro-enterprises are endengered to impact due to the tiny scale of it, but on the other hand micro-enterprises can be solution for family economy in the midway of the outbreak of Covid-19. The number of terminations causes a person to find a job in order to earn income for family. Government rgegulations on health protocols are continued and give impacts on economy. This study focuses to look for the impact of Covid-19 and PPKM on micro-enterprises in Serang Subdistrict, Serang City, Banten Province. The research was conducted on 36 micro businesses by conducting observations and interview about the issue. The outcome of this study is the negative impact of Covid-19 and the positive impact of PPKM on micro businesses. This proves that if Covid-19 rises, then micro-businesses decrease. However, not so with PPKM.